Predicting ZIS Institution Assets in Indonesia - Najiha, Izanatun; Wiranti, Dwi Sintia; Utami, Khofifah Pirda (Islamic Social Finance, 2025)
The Zakat, Infaq, and Alms (ZIS) industry in Indonesia has a strategic role in supporting social development and poverty alleviation. Along with the increasing public awareness of Islamic philanthropy, ZIS industrial assets show a significant growth trend year over year. This study aims to predict the development of total ZIS industrial assets in Indonesia in the coming period by using three forecasting methods, namely Trend Analysis (regress over time), Multiplicative Decomposition, and Exponential Smoothing with Trend. The data used is annual data on total ZIS industrial assets for the period 2002-2018 sourced from the Financial Services Authority (OJK). The results show that historically ZIS's industrial assets have increased significantly, from Rp68 billion in 2002 to Rp8,100 billion in 2018. The forecast results show that ZIS industrial assets are expected to continue to grow in the 2019–2023 period, despite variations in predictive values between methods. Based on the Mean Absolute Percentage Error (MAPE) indicator, the Trend Analysis and Multiplicative Decomposition methods show relatively better forecasting performance compared to the Exponential Smoothing with Trend method. These findings are expected to be a reference for regulators and managers of ZIS in formulating policies for the development of the Islamic philanthropic industry in Indonesia.